A Solvent-Free Electrode Coating Technique for All Solid State Lithium Ion Batteries. (7th July 2017) - Graebe, Heiko; Netz, Andreas; Baesch, Susanna; Haerdtner, V.; Kwade, Arno
Abstract : A solvent-free preparation technique of PEO/LiTFSI electrolytes and LFP-based cathodes is demonstrated. The mixing step is the most essential part in the process chain to achieve a free-flowing powder, which is the key for further process steps. The morphology of the powder has been investigated by SEM and EDX analysis. Symmetrical and full cells were built and electrochemically characterized. The measured ionic conductivity of the solvent-free prepared electrolytes is in the same range as for solvent-casted electrolytes. Cathodes prepared in a solvent-free manner show the typically observed charge and discharge potentials for the active material used in a solvent based processing route.